THE EFFECT OF CURCUMA ZEDOARIA EXTRACT ON LIVER DAMAGE BIOMARKERS IN A DIABETIC RAT MODEL - Nurdiana Maulia; Gradis Amalia; Muna Dasa Azizah; Aliya Syukur Widyasari; Hesa Haidar Ramadhani; Marshanda Hasna Pramesti; Sampurna Sampurna; Nurina Tyagita; Bagas Widiyanto (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Uncontrolled hyperglycemia in diabetes mellitus (DM) can cause liver tissue damage. This can be characterized by increased levels of several biomarkers, including transaminase and transferase enzymes and alpha-fetoprotein (AFP) level, as well as decreased bilirubin and albumin levels. White turmeric (Curcuma zedoaria) contains high levels of antioxidants and anti-inflammatory compounds. The objective of this study was to determine the effect of white turmeric extract on liver damage biomarkers in DM rats. This true experimental study used a post-test-only control group design. The test subjects were 28 male Wistar rats divided through two randomizations. In the first randomization, rats were allocated into two groups (control/K1 and the DM rat group) with a ratio of 1:3. DM was induced by an intraperitoneal injection of niacinamide (NA) 45 mg/kg BW followed by streptozotocin (STZ) 110 mg/kg BW 15 minutes later. The second randomization divided the DM rats into three groups: K2 (DM only), K3, and K4 (each receiving white turmeric extract at 9 and 18 mg/g BW, respectively) for 28 days. The next day, liver biomarkers were measured. A one-way ANOVA test for SGOT, GGT, AFP, and albumin levels showed p<0.05. Likewise, the Kruskal-Wallis test for SGPT and bilirubin levels also showed significant differences. The levels of SGOT, SGPT, GGT, AFP, bilirubin, and albumin differed significantly among the four groups. AFP and bilirubin levels in K4 were lower than in K3 and K2, while albumin levels were higher than in those groups. Administration of white turmeric extract reduced transaminase and transferase enzymes, bilirubin, and AFP, and increased albumin levels in DM Wistar rats. Keywords: diabetes mellitus, liver damage biomarkers, white turmeric DOI : 10.35990/mk.v9n1.p1-12